Z‐Selective α‐Arylation of α, β‐Unsaturated Nitriles via [3, 3]‐Sigmatropic Rearrangement. (24th November 2020) - Chen, Mengyuan; Liang, Yuchen; Dong, Taotao; Liang, Weijian; Liu, Yanping; Zhang, Yage; Huang, Xin; Kong, Lichun; Wang, Zhi‐Xiang; Peng, Bo
Abstract: The Morita‐Baylis–Hillman (MBH) reaction and [3, 3]‐sigmatropic rearrangement are two paradigms in organic synthesis. We have merged the two types of reactions to achieve [3, 3]‐rearrangement of aryl sulfoxides with α, β‐unsaturated nitriles. The reaction was achieved by sequentially treating both coupling partners with electrophilic activator (Tf2 O) and base, offering an effective approach to prepare synthetically versatile α‐aryl α, β‐unsaturated nitriles with Z ‐selectivity through direct α‐C‐H arylation of unmodified α, β‐unsaturated nitriles. The control experiments and DFT calculations support a four‐stage reaction sequence, including the assembly of Tf2 O activated aryl sulfoxide with α, β‐unsaturated nitrile, MBH‐like Lewis base addition, [3, 3]‐rearrangement, and E1cB‐elimination. Among these stages, the Lewis base addition is diastereoselective and E1cB‐elimination is cis ‐selective, which could account for the remarkable Z ‐selectivity of the reaction. Abstract : [3, 3]‐Sigmatropic rearrangement of aryl sulfoxides with α, β‐unsaturated nitriles has been developed by merging the Morita‐Baylis–Hillman reaction into the S(IV)‐mediated [3, 3]‐rearrangement process. The method enables the remarkable Z ‐selective synthesis of a wide variety of valuable α‐aryl α, β‐unsaturated nitriles that can be challenging to obtain by traditional synthetic methods.